Population dynamics of Scomberomorus brasiliensis from a small-scale fishery off Southern Brazil - Paulo de Tarso da Cunha Chaves; Pollyana Olbera Birnfeld; André Martins Vaz-dos-Santos (Ocean and Coastal Research)
Scomberomorus brasiliensis is the most important fish species of the small-scale fishery off the southwestern Atlantic north of the La Plata estuary. For management purposes, this study evaluated their reproductive biology, size, age and growth along the Paraná coast. Monthly samples (March 2018-June 2020) from the fishery comprised 933 specimens (413 males, 520 females), 210-779 mm fork length, corresponding to a size smaller than in the northern areas. It presented negative allometry (b = 2.69159, length-weight relationship). Specimens in all stages of maturity occurred during the study period, indicating spawning in the area from October to June, peaking from January to March. The gonad–length relationship was suitable to confirm this assessment. Individual fecundity varied between 34,484 and 390,786 oocytes. Maturity occurred at L50 = 446.46 mm, t50 = 1.4 years, and L100 = 588.79 mm, and t100 = 2.3 years. The growth parameters were L∞ = 771.68 mm, k = 0.65 year-1 and t0 = -0.102 years, with cohorts aged from 0.5 to 6.5 years. Scomberomorus brasiliensis along the Paraná coast constitutes a self-sustaining group, not directly related to that from northeastern Brazil. This small-scale fishery is not currently negatively affecting stock level; it is essential to monitor these attributes to detect future changes or impacts.